The subject of liberty : toward a feminist theory of freedom - Hirschmann, Nancy J. (Princeton University Press, 2003)
This book reconsiders the dominant Western understandings of freedom through the lens of women's real-life experiences of domestic violence, welfare, and Islamic veiling. Nancy Hirschmann argues that the typical approach to freedom found in political philosophy severely reduces the concept's complexity, which is more fully revealed by taking such practical issues into account. Hirschmann begins by arguing that the dominant Western understanding of freedom does not provide a conceptual vocabulary for accurately characterizing women's experiences. Often, free choice is assumed when women are in f.